Penerapan Flipped Classroom Berbantuan Microsoft Sway untuk Meningkatkan Kemampuan Berpikir Kritis Pada Pembelajaran PJOK - Chandra, Gusti Kade adi; Parwata, I Gusti Lanang Agung; Hidayat, Syarif (Jurnal Sporta Saintika, 2026)
Critical thinking skills are essential in twenty-first century learning, including Physical Education, Sports, and Health (PJOK). However, PJOK instruction, particularly in soccer passing material, often emphasizes physical activity with limited cognitive engagement. This study aimed to improve students’ critical thinking skills through the implementation of a Microsoft Sway–assisted flipped classroom learning model. This study employed Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 37 Grade XI IPS 2 students at SMA Negeri 6 Denpasar. Data were collected through observation and critical thinking assessment instruments. The results showed an improvement in students’ critical thinking skills, indicated by an increase in the mean score from 80.10 in Cycle I to 82.12 in Cycle II, categorized as good. These findings indicate that the Microsoft Sway–assisted flipped classroom model effectively enhances students’ critical thinking skills by promoting active, student-centered learning in PJOK instruction.